Unusual stereochemical outcome of radical cyclization: synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ramakrishna, G.; Tejwani, R. B.; Ravindranathan, T.; Kamat, Subhash K.; Rai, B.; Sivadasan, L.; Balakrishnan, K.; Ramalingam, S.; Deshpande, V. H. (Tetrahedron, 2005)
An enantioselective synthesis of (+)-biotin 1 starting from naturally available cysteine is described. The key steps are the unusual stereochemical outcome of radical cyclization of compound 10 to prepare 5,5-fused system 11, and the introduction of C4-sidechain at C-6 in 13 via a Grignard reaction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: biotin; exocyclization; radical cyclization